Increasing antimicrobial resistance in clinical isolates of Staphylococcus intermedius group bacteria and emergence of MRSP in the UK. (14th February 2015) - Beever, L.; Bond, R.; Graham, P. A.; Jackson, B.; Lloyd, D. H.; Loeffler, A.
Abstract : Frequencies of antimicrobial resistance were determined amongst 14, 555 clinical Staphylococcus intermedius group (SIG) isolates from UK dogs and cats to estimate resistance trends and quantify the occurrence of meticillin‐resistant Staphylococcus pseudintermedius (MRSP). Reports from two diagnostic laboratories (13, 313 general submissions, 1242 referral centre only submissions) were analysed retrospectively (2003/2006–2012). MRSP were defined by phenotypic resistance to meticillin and concurrent broad β‐lactam resistance; a subset was confirmed genetically (SIG‐specific nuc and mecA ). Trends were analysed by Cochran‐Armitage test. Resistance remained below 10 per cent for cefalexin, amoxicillin‐clavulanic acid and the fluoroquinolones. Increasing resistance trends were seen in both laboratories for ampicillin/amoxicillin (both P<0.001), cefovecin (both P<0.046) and enrofloxacin (both P<0.02). Resistance to cefalexin increased over time in referral hospital isolates (P<0.001) to clindamycin (P=0.01) and trimethoprim‐sulfamethoxazole (P=0.001) amongst general laboratory submissions. Overall, 106 MRSP were isolated (0.7 per cent of submissions) including 32 (2.6 per cent of submissions, all genetically confirmed) from the referral centre population (inter‐laboratory difference P<0.001). Against a background of widely susceptible SIG isolates, a new trend of increasing resistance to important antimicrobials was identified overtime and the emergence of MRSP from UK clinical cases was confirmed. Attention to responsible use of antibacterial therapy in small animal practice is urgently needed.